Clinical Utility of Precision Medicine in Pediatric Oncology: A Systematic Review. (2021) - Lee, Justin; Gillam, Lynn; Visvanathan, Keshini; Hansford, Jordan R.; McCarthy, Maria C.
Abstract : PURPOSE: Precision medicine uses advanced molecular techniques to guide the use of targeted therapeutic drugs and is an emerging paradigm in pediatric oncology. Clinical evidence related to the efficacy of many novel targeted drugs, however, is currently very limited given the rarity of pediatric cancer and the lack of published evidence for the use of these drugs in children. This systematic review aimed to evaluate the existing evidence for the feasibility and clinical efficacy of precision medicine in pediatric oncology. METHODS: A systematic review was conducted using the PubMed, Medline, and Embase databases. Clinical trials and observational studies, which used molecular assays such as whole-exome sequencing to identify molecular targets that guided the allocation of targeted cancer drugs and reported clinical outcomes, were included in this review. RESULTS: Twenty-one clinical trials and observational studies were identified, collectively enrolling 1, 408 pediatric patients across nine countries. Therapeutic targets were found in 647 patients (46.0%); however, only 175 of these patients (27.0%) received a targeted drug. Objective responses were recorded for 73 (41.7%) of these 175 patients, only 5.2% of the total sample. Inconsistent outcome reporting and limited comparison with conventional treatment hindered evaluation of the clinical utility of precision medicine. CONCLUSION: Precision medicine can feasibly identify molecular targets in a clinical setting. However, the inaccessibility of targeted drugs is a significant barrier, restricting the exploration of its therapeutic potential in pediatric oncology. Future clinical trials should endeavor to link the molecular testing results with access to targeted drugs and standardize outcome reporting to advance understanding of the benefits of this novel paradigm in improving patient outcomes.